2001
DOI: 10.1182/blood.v98.8.2448
|View full text |Cite
|
Sign up to set email alerts
|

The alternatively spliced αEC domain of human fibrinogen-420 is a novel ligand for leukocyte integrins αMβ2 and αXβ2

Abstract: The interaction of human plasma fibrinogen with leukocyte integrins ␣ M ␤ 2 (CD11b/ CD18, Mac-1) and ␣ X ␤ 2 (CD11c/CD18, p150,95) is an important component of the inflammatory response. Previously, it was demonstrated that binding of fibrinogen to these integrins is mediated by ␥C, the globular C-terminal domain of the ␥ chain. In this study, evidence was found of another fibrinogen domain that can serve as a ligand for the 2 leukocyte integrins: ␣ E C, a homologous domain that extends the ␣ chains in a recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 54 publications
0
40
0
1
Order By: Relevance
“…In RLTYAYFAG (Fig. 6A, spot 8), mutation of Arg to Glu reduced binding (spot 9) and additional mutations of Leu and Tyr created the completely inactive EATAAYFAG peptide (spots [11][12][13][14][15][16]. Taken together, these analyses identified several new ␣ M I-domain recognition sequences in ␥C and ␤C and provided preliminary insights into the ␣ M I-domain binding preferences.…”
Section: The ␣ M I-domain Interacts With Multiple Binding Sites In Thmentioning
confidence: 83%
See 2 more Smart Citations
“…In RLTYAYFAG (Fig. 6A, spot 8), mutation of Arg to Glu reduced binding (spot 9) and additional mutations of Leu and Tyr created the completely inactive EATAAYFAG peptide (spots [11][12][13][14][15][16]. Taken together, these analyses identified several new ␣ M I-domain recognition sequences in ␥C and ␤C and provided preliminary insights into the ␣ M I-domain binding preferences.…”
Section: The ␣ M I-domain Interacts With Multiple Binding Sites In Thmentioning
confidence: 83%
“…Second, deletion of P2 in ␥C decreased the ␣ M I-domain binding by only ϳ50% suggesting that one or more alternative sites participate in recognition (10). Third, the ␤C and ␣ E C domains of Fg, which share with ␥C only 39 and 40% sequence identity, respectively, and do not contain P2, bind the ␣ M I-domain (10,11). This further suggests that ␤C and ␣ E C also contain ␣ M I-domain recognition sites.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…Further evidence for the similarity of ligand specificity of integrins ␣ D ␤ 2 and ␣ M ␤ 2 was obtained in inhibition experiments using soluble peptide P2-C. We previously reported that P2-C inhibits ␣ M ␤ 2 -mediated cell adhesion not only to the ␥C domain of fibrinogen, from which this sequence is derived, but also to other fibrinogen domains 32 and to many unrelated proteins (Valeryi Lishko, unpublished data, June 2002). 27,33 P2-C was also an effective inhibitor of ␣ D ␤ 2 -mediated cell adhesion to vitronectin, fibrinogen, plasminogen, and VCAM-1 (Table 1).…”
Section: Analyses Of Ligand-binding Properties Of Integrinmentioning
confidence: 93%
“…Its structure has been elucidated through crystallography [6], but its functional characteristics have been poorly described. The EC region is susceptible to early proteolysis by plasmin [7] and can act as a ligand for neutrophils and monocytes via  M  2 and  X  2 integrins [8]. Fibrinogen EC has been shown to produce clots with thinner, more branched fibres with increased maximum amplitude in thromboelastometry, which is an indication of increased clot stiffness [9].…”
Section: Fibrinogen Ecmentioning
confidence: 99%